PERUBAHAN DAN KONTINUITAS POLA SPASIAL PADA RUMAH TINGGAL CINA DI SODITAN, KARANGTURI, DAN BABAGAN, LASEM - Prasetyaningsih, Yulyta Kodrat (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2007)
The study would analyze some factors underlying the spatial changes on Chinese houses and interprets what has influenced them. The focusing of study is interacting the Chinese houses's layout fromSoditan, Karangturi, and Babagan that has different periods. The study based on the field observation and in-depth interview has done in June 2004 is used toanalyze Chinese houses in Lasem. There is no hypothesis, this study is to increase understanding of the spatial pattern on Chinese houses where has gone through in life's changes. Spatial Syntax is used for analysis and interpretation of Chinese houses's layout. The spatial pattern was found by interacting the irreducible objects and related to each other onhuman spatial organization in all its variability.This part would discuss factor which implicate the changes of spatial pattern on Chinese houses in Soditan, Karangturi, and Babagan. The analysis generally found that first, the changing of time periods no implicate to spatial pattern onChinese houses in Lasem. There has still keeped of using main spatial pattern on their layout. Second, the changing orientation of Chinese houses from river to roads has no influenced the spatial pattern. Third, the changes of space just has been reducing space fromhigh complexityto bemore simplicity. Regularity spatial pattern on Chinese houses is the main spatial pattern that always on ringness dimension which are six spaces : front courtyard, front terrace, praying room (Ngetiya), living room, back terrace, and back courtyard. The pattern shows in a symmetric and distributed relationship, the higher hieararchi of space is located in living room (space F).Keyword: spatial pattern, chinese house